2001
DOI: 10.2528/pier01022603
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Rectangular Waveguide Junctions Containing Cylindrical Posts

Abstract: Abstract-Accurate determination of the generalized scattering matrix of the crossed waveguides junction, T -junction and right-angle bend containing a cylindrical post is presented. The generalized scattering matrix of the four port structure is obtained from those of the two ports right angle bend with different combinations of perfect electric and/or magnetic walls. The generalized scattering matrix of the right angle bend (quarter of the structure) is obtained by the mode matching method where the electroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Relations of continuity (16) allows amplitudes (V n ; I n ) to be defined in z = 0. A numerical integration leads to the amplitudes (V n ; I n ) in z = l. Relations of continuity (17) give the generalized voltages W The fourth order Runge-Kutta's method is chosen for numerical integrations from w = z = 0 to w = z = l. In references [2,3], we have shown that the amplitudes (V n ; I n ) and (V * n ; −I * n ) are solution of system (41). Using this property, we determine the multimodal scattering matrix with only N numerical integrations.…”
Section: Initial Value Problemmentioning
confidence: 99%
“…Relations of continuity (16) allows amplitudes (V n ; I n ) to be defined in z = 0. A numerical integration leads to the amplitudes (V n ; I n ) in z = l. Relations of continuity (17) give the generalized voltages W The fourth order Runge-Kutta's method is chosen for numerical integrations from w = z = 0 to w = z = l. In references [2,3], we have shown that the amplitudes (V n ; I n ) and (V * n ; −I * n ) are solution of system (41). Using this property, we determine the multimodal scattering matrix with only N numerical integrations.…”
Section: Initial Value Problemmentioning
confidence: 99%
“…To reach this goal, several solutions have been proposed in the technical literature in the past few years, thus giving rise to the so-called compensated turnstile junctions. Different compensation techniques have also been applied recently to the optimization of other multiport waveguide junctions, such as crossed waveguide junctions, T-junctions, right-angled bends and magic tees [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The correct analysis and design of these circuits is of great importance for many applications such as satellite and wireless communication systems [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%